Critical Factors for SMEs’ Business Sustainability through the COVID-19 Pandemic: A Systematic Literature Review - Friska Mastarida; Rini Setiawati (Bina Nusantara University, 2024)
The COVID-19 pandemic has brought profound changes in the global economy, altering the dynamics between nature, people, government, and business. This transformation has particularly impacted Small and Medium Enterprises (SMEs). As vital contributors to the distribution of wealth and the foundation of numerous businesses worldwide, SMEs face various challenges in sustaining their operations in today’s competitive and globalized economy. The research aimed to explore the factors influencing the sustainability of SMEs from the Resource-Advantage Theory of Competition (RAToC) perspective. It applied a qualitative research through bibliometric analysis using Visualization of Similarities (VOS) viewer software with Scopus data from 2019 to 2023 and resulted in 560 relevant articles. The literature review reveals that successful SMEs in the post-COVID-19 era are capable of addressing challenges through innovation, adaptability, flexibility, and resource integration with a commitment to social responsibility. The keys to their success are the adept embrace of technological advancements, responsiveness to market changes, proactive seizing of new opportunities, and the cultivation of stakeholder engagement alongside prudent risk management. The research not only provides a nuanced understanding of dynamic strategies, but also offers profound insights into essential attributes, positioning SMEs to succeed within the continually evolving post-pandemic landscape. Therefore, it ensures their resilience and sustained growth in the future.